Wind stress and near‐surface shear in the equatorial Atlantic Ocean. Issue 4 (19th February 2014) - Wenegrat, Jacob O.; McPhaden, Michael J.; Lien, Ren‐Chieh
Abstract The upper ocean response to wind stress is examined using 8 months of unique near‐surface moored velocity, temperature, and salinity data at 0°N, 23°W in the equatorial Atlantic. The effects of wind stress and shear on the time‐varying eddy viscosity are inferred using the surface shear‐stress boundary condition. Parameterizations of eddy viscosity as a function of wind stress and shear versus wind stress alone are then examined. In principle, eddy viscosity should be proportional to the inverse shear, but how it is represented implicitly or explicitly can affect estimates of the near‐surface flow field. This result may explain some discrepancies that have arisen from using parameterizations based only on wind stress to characterize the effects of turbulent momentum mixing.